Mechanical properties of supramolecular polymeric materials cross-linked by donor–acceptor interactions. Issue 26 (14th March 2019) - Itano, Misaki; Kobayashi, Yuichiro; Takashima, Yoshinori; Harada, Akira; Yamaguchi, Hiroyasu
Abstract : We prepare a tough elastomer with aromatic donor and acceptor molecules introduced on the same polymer side chain. Abstract : We prepared polymeric materials cross-linked by donor–acceptor (DA) interactions between pyrene (Py) and trinitrobenzene (TNB) on the same polymer side chain. Although a mixture of a Py polymer and a TNB polymer did not form an elastomer, a polymer bearing DA units on the same polymer chain formed an elastomer. The fracture energy of the elastomer was higher than that of the covalently cross-linked elastomer.